Pengaruh Ukuran Perusahaan, Profitability, Leverage, Dewan Direksi, dan Gender Board Terhadap Intellectual Capital Disclosure Perusahaan Keluarga di Indonesia - Chen, Ariel Valentine Sanjaya; Merawati, Luh Komang; Dicriyani, Ni Luh Gde Mahayu (Juara: Jurnal Riset Akuntansi, 2024)
In Indonesia itself, attention to Intellectual Capital (IC) grew after the emergence of PSAK No. 19 (revised 2015) concerning intangible assets. Based on PSAK No. 19, intangible assets are non-monetary assets that can be identified and have no physical form. This research was conducted to determine the effect of Company Size, Profitability, Board of Directors, Gender Board, Leverage on Intellectual Capital Disclosure of Family Companies in Indonesia. The population in this research are annual reports from sector companies listed on the Indonesia Stock Exchange (BEI) with a time span of 2020 to 2022. The sample used in this research was selected using a purposive sampling technique with a sample size of 54 family companies. The data analysis technique used in this research is multiple linear regression. Based on the research results, it can be seen that gender board has a positive effect on IC disclosure. Variable of company size, profitability, board of directors and leverage has no effect on IC disclosure.